INVESTIGATING THE CORRELATION BETWEEN JOB SATISFACTION, AUTONOMY , AND SELF-EFFICACY AMONG SCHOOL NURSSES IN BAHRAIN - Dr Fatin Hasani. RN, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
This paper sought to establish factors associated with job satisfaction among nurses, the role of the school nurse in Bahrain, as well as the relationship between autonomy, self-efficacy and job satisfaction. The study employed a mixed approach to establish the major findings highlighted in the study. Questionnaires and interviews were used to collect relevant data for the study. The SPSS software and thematic analysis were used to analyze the data. According to the study, school nurses play various roles, including preparing clinics, providing medical services to students, conducting health education and awareness among students and staff and participating in health committees. The study noted significant relationships between autonomy, self-efficacy and job satisfaction. Overall, job satisfaction, autonomy, self-efficacy played an important role in enhancing the performance of nurses.